Legal Competency in a Case of Pedophilia: Advertising on the Internet - Fontana-Rosa, Julio César (International journal of offender therapy and comparative criminology, 2001)
The author discusses the importance of the Internet in disseminating advertising matter targeted to stimulate interest in pedophilia. The case of a suspect held in custody for using the Internet for this end is presented. The case is considered in light of the current literature that regards pedophilia as a pathological entity. As such, the author proposes that pedophilia should be considered a mental disorder in legal terms. Besides the pedophilic-child binomial, he discusses the exploiter who is not affected by pedophilia but takes advantage of the Internet for profit. Because of the repugnancy that pedophilia causes, social pressure to apprehend the offenders is intense and can cause witch hunting, both of the pedophile, who is a person with a psychological disorder, and of the exploiter, who may be indirectly responsible for such conduct. Societal pressure sometimes looms over forensic medical judgment, and the author suggests the possibility of justice giving in to such pressures